A case report on management of cervical insufficiency using Chhattisgarh balloon in second trimester cerclage for fetal membrane prolapse - Shefali Tyagi; Swapnil Bhagat; Shreeja Karan (Barpeta Obstetrics and Gynaecological Society, 2019)
Many second trimester miscarriages and neonatal deaths are caused by cervical incompetence. In second trimester if the membranes prolapse in vagina due to cervical incompetence it can be technically very difficult for the clinician to push the membranes back in cervix and apply cerclage to prolong the pregnancy. We present a case of 30 year old primi gravida who came to emergency at 22 weeks of gestation with cervix dilated to 4 cms and membranes prolapsing till the vagina. After ruling out possibility of infection, decision for rescue cerclage was taken. The membranes were deposited back in the uterus with help of Chhattisgarh balloon and Mac Donald's stitch was applied. Patient could successfully carry her pregnancy till 35 weeks and baby did not need NICU admission. Chhattisgarh balloon can be a useful tool in low resource country like India where it can be easily prepared, inexpensive and less traumatic compared to other alternatives available as of now.